Особенности современной социальной трансформации - Ємельянова, Юлія Павлівна; Yemelianova, Yuliia P.; Емельянова, Юлия Павловна (Дніпропетровський національний університет імені Олеся Гончара, 2012)
В статье анализируются некоторые аспекты социальной трансформации на рубеже ХХ-ХХI столетий.

Certain aspects of social transformation at the turn of the 20th-21st centuries are analyzed in this article.
Special features (peculiarities) of modern social transformation
Keywords: социальная реальность; социальность; социальное; этничность; трансформация; social reality; sociality; social; ethnicity; transformation